2013
DOI: 10.1089/scd.2012.0455
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Retardation-Associated Protein srGAP3 Regulates Survival, Proliferation, and Differentiation of Rat Embryonic Neural Stem/Progenitor Cells

Abstract: The mental retardation-associated protein, srGAP3 is highly expressed in neurogenic sites. It is thought to regulate the key aspects of neuronal development and functions. Little is known about the interaction between srGAP3 and immature neural stem cells/neural progenitor cells (NSCs/NPCs). In the current study, the expression of srGAP3 in NSCs/NPCs was detected. Then, survival, proliferation, differentiation, and morphological alteration of NSCs/NPCs were assessed after a lentivirus-mediated knockdown of srG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…NSCs/NPCs were isolated from cerebral cortex of rat embryos on embryonic day 14 (E14) to 15 (E15) and cultured in serum-free growth medium following the protocol of Gage et al (1995) and optimized in our lab (Lu et al, 2011, 2013). NSCs/NPCs growth medium contains DMEM/F12 (Dulbecco’s modified Eagle medium and Ham’s F12, 1:1), 10 ng/mL bFGF, 20 ng/mL EGF, 100 U/mL penicillin, 100 μg/mL streptomycin, 1% N2 and 2% B27 supplement (all from Invitrogen, Carlsbad, CA, USA) and 2.5 μg/mL heparin (Sigma, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NSCs/NPCs were isolated from cerebral cortex of rat embryos on embryonic day 14 (E14) to 15 (E15) and cultured in serum-free growth medium following the protocol of Gage et al (1995) and optimized in our lab (Lu et al, 2011, 2013). NSCs/NPCs growth medium contains DMEM/F12 (Dulbecco’s modified Eagle medium and Ham’s F12, 1:1), 10 ng/mL bFGF, 20 ng/mL EGF, 100 U/mL penicillin, 100 μg/mL streptomycin, 1% N2 and 2% B27 supplement (all from Invitrogen, Carlsbad, CA, USA) and 2.5 μg/mL heparin (Sigma, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Immunocytochemistry staining was performed following standard protocol and optimized in author’s laboratory (Lu et al, 2011, 2013). Primary antibodies, including monoclonal mouse anti-nestin (1:200, Millipore, Temecula, CA, USA), monoclonal mouse anti-β-tubulin III (1:200, Millipore, Temecula, CA, USA) and monoclonal mouse anti-GFAP (1:500, Millipore, Temecula, CA, USA) were used to identify NSCs/NPCs, neurons, astrocytes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A first analysis of the gross morphology of the DG revealed that the thickness of the granule layer was not significantly altered in SrGAP3-deficient mice, indicating that no major cell loss occurred in this area. However, it might be possible that adult neurogenesis within the hippocampus is affected in these mice, since it has been shown that knockdown of SrGAP3 down-regulates the number of cortical neuronal stem cells, derived from embryonic rats (E14) in vitro (Lu et al 2013). Furthermore, conditional SrGAP3 knockout mice were previously shown to display mislocated DCX positive cells in the corpus callosum that are thought to stem from the subventricular zone (Kim et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown in vitro that lentivirus-mediated knockdown of SrGAP3 dramatically decreases viability and proliferation of cortical immature neural stem cells/neural progenitor cells (Lu et al 2013). Aside from the SVZ, the dentate gyrus (DG) is also capable of adult neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins were identified as the downstream regulators of the Slit and Robo receptor system and are important in numerous developmental processes in diverse cell types (13). During neural development, srGAP1, 2 and 3 are widely expressed in the nervous system and function as multifunctional adaptor proteins involved in neuronal migration, neuronal morphogenesis, neurite outgrowth and synaptic plasticity (1,38). …”
Section: Introductionmentioning
confidence: 99%